2017
DOI: 10.4103/ijpc.ijpc_100_17
|View full text |Cite
|
Sign up to set email alerts
|

Complementary therapies for symptom management in cancer patients

Abstract: Cancer patients are often poly-symptomatic which distressingly affects their quality of lives (QOLs). Alhough, conventional management provides adequate symptom control, yet is coupled with some limitations. Complementary therapies (CTs) have shown beneficial effects in cancer patients for symptomatic relief. The aim of this article is to provide evidence-based review of commonly used CTs for symptom management in cancer care. Hypnosis has promising evidence to be used for managing symptoms such as pain, chemo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 160 publications
1
28
0
3
Order By: Relevance
“…Additionally, a growing body of empirical data supports the use of psychosocial interventions for the management of CRF (Goedendorp at al., 2009;Minton, Jo, & Jane, 2015). Empirical literature has demonstrated that complementary therapies are somewhat beneficial in ameliorating CRF (Finnegan-John, Molassiotis, Richardson, & Ream, 2013;Satija & Bhatnagar, 2017).…”
mentioning
confidence: 99%
“…Additionally, a growing body of empirical data supports the use of psychosocial interventions for the management of CRF (Goedendorp at al., 2009;Minton, Jo, & Jane, 2015). Empirical literature has demonstrated that complementary therapies are somewhat beneficial in ameliorating CRF (Finnegan-John, Molassiotis, Richardson, & Ream, 2013;Satija & Bhatnagar, 2017).…”
mentioning
confidence: 99%
“…Acupuncture, which is one of the important elements of traditional Chinese medicine, is a scientific treatment that enables the body to regain its balance as a result of stimulation of special points in the body with needles. Acupuncture is effective in reducing chronic pain in cancer patients by exerting secretion of enkephalins and increasing serotonin levels from endogenous opioids known to have an effect on regulating mental and psychological state [33][34][35]. In studies with cancer patients with pain, acupuncture has been found to be a complementary, self-medicating, nonmedication treatment that reduces cancer-related symptoms (pain, digestive problems, neuropathy), and is selfmedicating [36][37][38][39].…”
Section: (Ii) Acupuncturementioning
confidence: 99%
“…With the advent of newer and efficient diagnostic techniques and therapeutic modalities, the number of people living with cancer are increasing. [ 1 ] Pain is one of the most common symptoms reported by patients during the disease trajectory. [ 2 ] It affects nearly 39%–66% patients during various stages of disease and treatment.…”
Section: Introductionmentioning
confidence: 99%